Kudeta Militer di Myanmar dan Prinsip Non-Intervensi ASEAN - Rozak, Abdur (CV. Ulil Albab Corp, 2024)
This article explains the Military Coup in Myanmar and the ASEAN Non-Intervention Principles. This research uses literature study. The conflict resolution mechanism in ASEAN is in accordance with the principles of the ASEAN charter, in which the principle of non-intervention is the main basis for resolving conflicts that occur in its member countries. However, in its development the principle of non-intervention became rigid and actually sabotaged joint efforts to defend human rights in these countries, including in the case of this coup conflict.